Oxygen vacancy ordering in SrFe0.25Co0.75O2.63 perovskite material. Issue 5 (18th January 2017) - Fernández Sanjulián, Javier; Chennabasappa, Madhu; García-Martín, Susana; Nénert, Gwilherm; Wattiaux, Alain; Gaudin, Etienne; Toulemonde, Olivier
Abstract : An oxygen-vacancy ordering related to the "314" model known for the Sr3 Y1 Co4 O10.5 oxide is proposed for Sr4 FeCo3 O10.52 material despite there is neither A-site ordering nor A-site mismatch. Abstract : SrFe0.25 Co0.75 O2.63 was synthesized by a solid-state reaction. Its structural study at room temperature using conventional X-ray as well as neutron powder diffraction, electron diffraction and high-resolution transmission electron microscopy is presented. An oxygen-vacancy ordering related to the "314" model known for the Sr3 Y1 Co4 O10.5 oxide is proposed despite neither an A-site ordering nor an A-site mismatch. By means of Mössbauer spectroscopy, Mohr salt titration and the difference in the neutron cross sections of Fe and Co, a cation distribution within the crystallographic sites as the following Sr4 (Fe0.14 3+ Co0.36 3+ )4 8 h (Fe0.11 4+ Co0.14 4+ Co0.25 3+ )4 8 f O10.52 is suggested, highlighting a natural layered structure with Fe and Co in higher oxidation states in the oxygen replete layers than in the oxygen deficient ones.